The taxation-growth-nexus revisited - K. Peren Arin; Michael Berlemann; Faik Koray; Torben Kuhlenkasper (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2011)
One of the major challenges of empirical tax research is the identification and calculation of appropriate tax data. While there is consensus that average marginal tax rates are most suitable for studying the effects of tax policy on economic growth, due to data limitations the calculation of marginal tax rates has been limited to the U.S. and the U.K. This paper provides calculations of average marginal tax rates for the four Scandinavian countries using the methodologies of Seater [1982, 1985] and Barro and Sahasakul [1983, 1986]. Then, by pooling the newly calculated tax rates for the Scandinavian countries with the data for the U.S. and the U.K., we investigate the effects of tax policy shocks on the per capita GDP growth rate. Our results suggest that an increase in average marginal tax rates has a negative impact on economic growth. Employing Additive Mixed Panel Models with penalized splines as estimation approach, we show that changes in tax rates have nonlinear effects. Increasing average marginal tax rates turn out to be the most distorting at relatively moderate tax rates.
Keywords: E62; H30; 330; Average marginal tax rates; tax policy; economic growth; panel data analysis; additive mixed models